Local Fourier Analysis for Edge-Based Discretizations on Triangular Grids. Issue 1 (3rd March 2015) - Rodrigo, Carmen; Sanz, Francisco; Gaspar, Francisco J.; Lisbona, Francisco J.
Abstract: In this paper, we present a local Fourier analysis framework for analyzing the different components within multigrid solvers for edge-based discretizations on triangular grids. The different stencils associated with edges of different orientation in a triangular mesh make this analysis special. The resulting tool is demonstrated for the vector Laplace problem discretized by mimetic finite difference schemes. Results from the local Fourier analysis, as well as experimentally obtained results, are presented to validate the proposed analysis.